In this problem, we are applying function notation. When we see a function written as
![f(x),](https://img.qammunity.org/2023/formulas/mathematics/college/o1apcq8rbnvcbity3krc7q13yctpy9sb1x.png)
we read it as "f of x" or "f as a function of x."
We will take the value of x and substitute it into the quation.
The function rule states
![f(x)=-2x+3](https://img.qammunity.org/2023/formulas/mathematics/college/mi9elb50uhc1kbl9o90ch0mqnwwd7btg7h.png)
Since we are given f(-3), we will substitute each x-value (inside parentheses), and simplify:
![f(-3)=-2(-3)+3=6+3=9](https://img.qammunity.org/2023/formulas/mathematics/college/rc73s6u6rkmwx78xsknp7hjd17ty0e0cij.png)
Therefore, f(-3) = 9.